Aktualisasi Ajaran Ahlussunah Wal Jamaah bagi Mahasantri Mabna Ummu Salamah UIN Malang - Rahmatya Azza Putri Nabila; Renggo Dian Sasi; M. Imamul Muttaqin (La-Tahzan: Jurnal Pendidikan Islam, 2025)
This research is motivated by gaps or challenges in applying the values and teachings of Ahlussunah Wal Jamaah (Aswaja) in the daily life of mahasantri in Mabna Ummu Salamah UIN Malang. This study aims to explore and analyze how mahasantri in Mabna Ummu Salamah Pusat Ma'had Al-Jamiah UIN Maulana Malik Ibrahim Malang actualize the teachings of Ahlussunah Wal Jamaah in their daily lives. This study uses a qualitative approach with participatory observation techniques and in-depth interviews with a number of mahasantri. The research findings reveal that the mahasantri in Mabna Ummu Salamah actively apply the teachings of Ahlussunah Wal Jamaah in their religious activities and daily lives. The form of actualization is applied whether through activities such as routine recitation, congregational prayer, dhikr, or also reflected in social ethics, leadership, or tolerance in the dormitory. They show sincerity in understanding and practicing the principles of this teaching, including adherence to the Quran and Sunnah, respect for scholars, and tolerance for differences of opinion. In addition, this study also identifies factors that influence the process of actualizing Ahlussunah Wal Jamaah teachings among mahasantri, including the educational environment, social influences, and the support of Islamic educational institutions.